решите систему уравнений: 1)x^2-4xy+y^2=6 b 2) y-2x=3

решите систему уравнений: 1)x^2-4xy+y^2=6 b 2) y-2x=3

  • x^2-4xy+y^2=6 y=2x+3

    y-2x=3 x^2-4x(2x+3)+(2x+3)=6

    x^2-8x^2-12x+4x^2+12x+9=6

    -3x^2=-3

    x^2=1

    x1= 1 x2=-1

    y=2x+3

    y1=2*1+3 y2=2*(-1)+3

    y1=5 y2=1

    Ответ: (1;5) ; (-1;1)

  • x^2-4xy+y^2=6; y^2-4xy+4x^2-3x^2=6; (y-2x)^2-3x^2=6

    ПОдставим вместо y-2x, тройку получим 9-3x^2=6,

    3x^2=3

    x^2=1

    x=+-1

    Но y=3+2x

    Получаем решения: (1;5) (-1,1)